Promising Anti-MRSA Activity of Brevibacillus sp. Isolated from Soil and Strain Improvement by UV Mutagenesis - Nuttapon Songnaka; Monthon Lertcanawanichakul; Apichart Atipairin (MDPI AG, 2020)
Antibiotic-resistant infection is a major health problem, and a limited number of drugs are currently approved as antibiotics. Soil bacteria are promising sources in the search for novel antibiotics. The aim of the present study is to isolate and assess soil bacteria with anti-MRSA activity and improve their capabilities by UV mutagenesis. Soil samples from the upper south of Thailand were screened for antibacterial activity using the cross-streak method. Agar well diffusion was used to examine the activity of isolates against a spectrum of human pathogens. The most active isolate was identified by 16S rRNA sequencing, and the production kinetics and stability were investigated. The most promising isolate was mutated by UV radiation, and the resulting activity and strain stability were studied. The results show that isolates from the cross-streak method could inhibit Staphylococcus aureus TISTR 517 (94 isolates) and Escherichia coli TISTR 887 (67 isolates). Nine isolates remained active against S. aureus TISTR 517 and MRSA, and eight isolates inhibited the growth of E. coli TISTR 887 as assessed using agar well diffusion. The most active strain was Brevibacillus sp. SPR-20, which had the highest activity at 24 h of incubation. The active substances in culture supernatants exhibited more than 90% activity when subjected to treatments involving various heat, enzymes, surfactants, and pH conditions. The mutant M201 showed significantly higher activity (109.88-120.22%) and strain stability compared to the wild-type strain. In conclusion, we demonstrate that soil Brevibacillus sp. is a potential resource that can be subjected to UV mutagenesis as a useful approach for improving the production of anti-MRSA in the era of antibiotic resistance.